HALAL TOURISM: AN EMPIRICAL EXAMINATION OF TOURIST MOTIVATION IN ACEH - Ricky Alfanda; Jasman J. Ma’ruf, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Tourism industries are always searching for a new customer segment. Over the last decade, one relatively unexplored segment in tourism industries is the ‘Religiously conscious’ tourist. Evidence indicates that some tourists feel they have no other choice but to compromise their religious beliefs in order to enjoy tourism. The objectives of this study are to determine the dominant factors of the push and pull factors and attributes of religion to the motivation of Muslim tourists to visit Aceh. The variable ‘Islamic Atribut’ is represented by the availability of Islamic norms and practices relevant to tourism at the destination. A conceptual model is developed and tested in 378 samples of domestic and foreign tourists in Aceh. Data that used in this study is primary data in form of questioner with Likert scale. SPSS 22.0 was used to analyze demographic characteristics of the respondents and hypothesis testing. The result of the research is that from 30 items statement of push factor, there are eight dominant new factors. Furthermore, of the 32 items of pull factor statements were nine new and dominant factors and from 18 items of Islamic attribute statements found three dominant new factors. The new factor formed is the grouping of the initial items on each variable. With this research, it is expected that stakeholder of halal tourism in Aceh can pay attention to dominant factors in the variable of push factor, pull factor and attribute of Islam as a means of identification of desire and requirement of Muslim traveler. So that Aceh tourism has a good competitive competitiveness and able to realize the vision of Aceh as a leading tourist destination of halal in Southeast Asia 2020.